Ball milling effects for induced carriers and reduced grain size on thermoelectric properties in Bi1−xSrxCuSeO. (5th October 2016) - Mizuno, Shu; Ishizawa, Mamoru; Fujishiro, Hiroyuki; Naito, Tomoyuki; Katsui, Hirokazu; Goto, Takashi
Abstract: We have investigated the ball milling effects for thermoelectric Bi1− x Sr x CuSeO materials. The characteristic rotation speed R for the ball milling exists, at which the crystallite size of the starting powder suddenly decreased. The grain size in the bulks sintered using ball-milled powders also decreased and thermoelectric properties were enhanced mainly by the induced carriers, rather than by the reduction in thermal conductivity. The ball milling effects of carrier doping on thermoelectricity are discussed.